Aroilbis(N,N-dietiltioureatos) de cádmio (II) e chumbo (II): síntese e caracterização - Wioppiold, Thomaz Arruda (2014)
This work introduces the synthesis of two novel ligands belonging to the aroylbis(thiourea) class to study the spacer group influence in the complexes structure. Five membered rings were utilized as spacer groups such as pyrrole and furan. The presence of the hydrogen in the pyrrole s nitrogen restricts the complexes formation while the furan ring, in some cases, can coordinate its oxygen atom to coordination with specific metals. It was synthetized bi-, tri-, tetranuclear complexes with two metal, cadmium and lead. With cadmium there was the formation only of binuclear compounds. The influence of heteroatom in the cadmium complexes was seen in the metal coordination number and in the formation of a decomposition product. Instead the lead complexes show a big structural heteroatom influence. With the pyrrol ligand had the formation of the binuclear compound while the furan ligand was formed a tetranuclear compound. The PbII and furan ligand also can form a trinuclear compound in the presence of another divalent metal such BaII and MnII. This complexes look like the literature complexes, however the donation of furan s oxygen is weaker in comparison with the pyridine s nitrogen what results in a decrease of the simmetry of this compounds.